KONSEP WISATA HALAL DI PONDOK PESANTREN - Buntoro, Fuad; Maisaroh, Siti (Universitas Mathla’ul Anwar Banten, 2023)
Halal tourism is a form of culture-based tourism that prioritizes the values ​​and norms of Islamic law. Halal tourism is very suitable to be implemented in various Islamic boarding schools because Islamic boarding schools already have an Islamic education label that applies Islamic norms. The existence of halal or sharia tourism in Islamic boarding schools will carry out the function of Islamic boarding schools as centers of local community empowerment. The typology of Islamic boarding school halal tourism can imitate the typology of tourist villages based on the characteristics of the resources and their uniqueness which can be grouped into 4 (four) categories; based on the uniqueness of local cultural resources, based on the uniqueness of natural resources, based on the combination of unique cultural and natural resources and based on the uniqueness of creative economic activities.